Patents and public health : legalising the policy thoughts in the Doha TRIPS Declaration of 14 November 2001 - Law, Andrew (MIPLC studies, 2009)
Do patents rules prevent countries from acquiring affordable medicines? A number of legal experts and governments have felt that the WTO, in particular the TRIPS Agreement, forces countries to favour patents over public health. The WTO sought to settle this dispute by concluding the Public Health Declaration. This book closely analyses the legal situation within the WTO prior to the Declaration and the consequences that resulted from it. It discusses the value of the changes, nationally and internationally, and the extent to which it makes the access to medicines more affordable. This review addresses not only the mere assessment of the positions of pro-patent countries but also takes a look at the obligations that developing countries have internationally and to their citizens. The analysis in this book is a comprehensive aid to lawyers as it explains the scope and purpose of the TRIPS Agreement provisions. It assists politicians and lobbyists by demystifying the treaty texts and by indicating the boundaries of lawful governmental action. Public Health representatives will be able to use this book to implement health care measures in a lawful way, both nationally and internationally.